AI and Data-Driven Brand Decisions: Influence on the Competitive Advantage in the Luxury Goods Industry - Vazhitova, Karina (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines how artificial intelligence (AI) and data-driven brand strategies can create a competitive advantage in the luxury goods industry. As more luxury brands integrate AI technologies into their operations, understanding how this impacts strategic brand decisions is limited, particularly in product development, marketing, consumer engagement, and pricing. This study uses a mixed-methods approach, combining a quantitative survey of 361 consumers and qualitative interviews with 12 industry experts from key departments at luxury brands, including marketing, customer relationship management, product development, data science, and e-commerce, to better understand these dynamics. Quantitative data shows that 78% of consumers have used AI features when purchasing luxury goods, with the majority stating that their satisfaction and brand loyalty have increased. Additionally, 71% of respondents said that AI-powered personalization had impacted their loyalty, and 68% said they were more likely to purchase from brands that used AI technology. Qualitative interviews also supported these findings, highlighting that AI is a strategic enabler rather than a replacement for creativity or human-computer interaction. Respondents highlighted the role of AI in predictive analytics, consumer targeting, trend forecasting, and personalization as ways to drive market differentiation and improve operational efficiency. Strong support is provided for both hypotheses by the findings of the study. Personalized services increase customer satisfaction and loyalty, as well as data-driven strategies help brands preserve their heritage while still maintaining a competitive advantage. Based on these insights, the study proposes a conceptual framework to help responsibly and effectively integrate AI into luxury brand strategies. This research offers a theoretical and practical contribution that illustrates how luxury brands can leverage AI technologies to enhance brand loyalty, enhance customer experience, and maintain long-term competitiveness in the evolving digital marketplace.